Reducing the health effect of natural hazards in Bangladesh - Mallick, Fuad Hassan; Cash, Richard A; Halder, Shantana R; Husain, Mushtuq; Islam, Md Sirajul; May, Maria A; Rahman, Mahmudur; Rahman, M Aminur (© 2013 Published by Elsevier Inc., 2016)
This article was published in the Lancet [©2013 Published by Elsevier Inc.] and the definite version is available at: http://dx.doi.org/10.1016/S0140-6736(13)61948-0 The article website is at: http://www.sciencedirect.com/science/article/pii/S0140673613619480